2018
DOI: 10.17159/2309-8309/2018/v17n4a1
|View full text |Cite
|
Sign up to set email alerts
|

An audit of circular external fixation usage in a tertiary hospital in South Africa

Abstract: Background: Circular external fixation is a well-known treatment modality in reconstructive orthopaedic surgery and is frequently used for deformity correction, limb lengthening, limb salvage, and complex diaphyseal and periarticular fractures. The current use of this treatment modality in the South African context remains largely unknown. This retrospective review aims to describe the indications, outcomes and complications of the use of circular external fixation in a tertiary hospital in South Africa. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A study conducted by Van der Walt and Ferreira however reported higher union rates of 100% using circular external fixators in their gunshot-induced tibia fracture sample. 21 The lower union rate with the use of circular external fixation observed in the present study may be attributed to the injury characteristics and delay in treatment for patients who were managed with this fixation modality. Furthermore, circular external fixation showed the highest FRI rates when compared to other definitive fixation methods, keeping in mind that circular fixation was reserved for patients with significant soft tissue injury or delay to surgery.…”
Section: Discussionmentioning
confidence: 60%
“…A study conducted by Van der Walt and Ferreira however reported higher union rates of 100% using circular external fixators in their gunshot-induced tibia fracture sample. 21 The lower union rate with the use of circular external fixation observed in the present study may be attributed to the injury characteristics and delay in treatment for patients who were managed with this fixation modality. Furthermore, circular external fixation showed the highest FRI rates when compared to other definitive fixation methods, keeping in mind that circular fixation was reserved for patients with significant soft tissue injury or delay to surgery.…”
Section: Discussionmentioning
confidence: 60%
“…It is well known that fractures of the shaft of the tibia often heal with some angulation, and although the amount of residual deformity that can be accepted is controversial, varus malalignment has been recognized as a cause of osteoarthritis in the medial compartment of the knee [15,16]. Some authors reported a rate of malunion with Ilizarov fixator ranging from 2% to 21.5% [17][18][19], probably due to either inadequate reduction in the fracture before fixation or loss of wire tensioning and subsequent loss of reduction [16,20]. Li et al [21] performed a systematic review and meta-analysis of peer-reviewed published studies on tibial plateau fractures treated with either open reduction with internal fixation (ORIF) or circular external fixation to compare functional, radiological outcomes, postoperative complications, and reoperation rates between the two methods.…”
Section: Discussionmentioning
confidence: 99%